Exogenous substrates as energy source for the contractile activity of the isolated rat tail artery. (Revista Española de Fisiología, 1996)
The isolated rat tail artery underwent a pronounced depression of the contractile responses to adrenaline during the incubation in a glucose-free medium containing 2-deoxyglucose and/or oxfenicine in order to inhibit the utilization of glycogen and/or endogenous triacylglycerol. When glucose was returned after 90 min of exposure to oxfenicine, the contraction strength recovered completely. In the medium with 2-deoxyglucose the addition of palmitate or hexanoate produced a recovery level 28% and 16% below the control values respectively. The effect of palmitate was nearly abolished and that of hexanoate partially decreased in the medium containing both inhibitors. Under this condition pyruvate reestablished the extent of the contraction to about 80% of the control value whereas beta-hydroxybutyrate produced a weak and transient recovery. These data suggest that in the tail artery the major portion of the energy needed to sustain the contractile activity is supplied by the oxidation of the more important plasmatic substrates with the exception of ketone bodies. However the Embden-Meyerhof pathway seems necessary to maintain at least a fraction of the contraction strength.